Translational switching from growth to defense – a common role for TOR in plant and mammalian immunity? - Zanetti, María Eugenia (2017)
Characterization of mRNA populations associatedwith the translational machinery (translatome)is shedding light on the molecular mechanisms ofplant environmental responses. The work presentedby Meteignier et  al. (2017) describes how selectivechanges in translation modulate the transitionfrom growth to defense responses in Arabidopsis,revealing new similarities between plant and animalimmunity.